A uniform measurement expression for cross method comparison of nanoparticle aggregate size distributions1. Issue 15 (7th August 2015) - Dudkiewicz, Agnieszka; Wagner, Stephan; Lehner, Angela; Chaudhry, Qasim; Pietravalle, Stéphane; Tiede, Karen; Boxall, Alistair B. A.; Allmaier, Guenter; Tiede, Dirk; Grombe, Ringo; von der Kammer, Frank; Hofmann, Thilo; et al.
<x xml:space="preserve">Abstract</x> Measurement methods produce incomparable results when applied to aggregated nanoparticles.